Kremenets «Prosvita» of the interwar period: public history - Iryna Skakalska (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2023)
In the research the author reveals the methods of public history that must be used to popularize the history of Kremenets «Prosvita» of the interwar period of the 20th century. Public history provides opportunities to learn about our past for a wide range of citizens. Among the latest scientific works, in which the activities of «Prosvita» are covered with varying degrees of completeness, it is necessary to name the researches of I. Zuliak, Yu. Kramar, L. Strilchuk, M. Kucherepa, and others. The purpose of the publication is to consider the activities of Kremenets «Prosvita» with Public History, which allows not only to gain a deeper understanding of historical processes, but also to promote the achievements of the society in the present. Kremenets «Prosvita» was founded in 1918, but was officially registered in 1920, ceased its activity in 1932, after being closed by Polish authorities. Quite quickly, the company created an extensive network of branches in Kremenets district. There were reading houses in every village, they had their own small libraries and subscribed to periodicals. Today, more than ever during the Russian-Ukrainian war; the work of enlightened people is needed, especially among internally displaced persons (for learning the Ukrainian language, Ukrainian history, popularizing Ukrainian literature, etc.). The experience of enlightened people of the interwar period of the 20th century should be useful for contemporaries. It is clear that not everyone will be able to read and study academic history, but Public History will come in handy. Historical knowledge does not always have to adhere to the academic form of presentation, just so that there are no falsifications. Public History will help to get a modern idea of how enlightened people worked in Kremenets in the interwar period. On the basis of the analysis of the numeral facts of the activities of enlightened people, it can be stated that «Prosvita» society had a significant impact on the development of national culture, education, and literature in Volyn. Among the famous educators of Kremenets district, it is necessary to promote the activities of B. Kozubskyi, S. Zhuk, M. Cherkavskyi, A. Zhyvotko, and others. Thus, highlighting the organization of the work of Kremenets «Prosvita» in the public space with the involvement of professional historians and representatives from outside the academic history is an important step for the popularization of the association.